2021
DOI: 10.3390/ijerph18084199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meridian Acupressure on Stress, Fatigue, Anxiety, and Self-Efficacy of Shiftwork Nurses in South Korea

Abstract: Shiftwork nurses experience physical and psychological health problems related to shift work. This study aimed to examine the effects of Meridian acupressure on stress, fatigue, anxiety, and self-efficacy of shiftwork nurses in South Korea. A quasi-experimental pretest-posttest control group design was employed. Study participants were a total of 59 shiftwork nurses (intervention group: n = 29, control group: n = 30) in S hospital, Seoul, South Korea. The study was conducted at nurse stations in S hospital. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…For example, one study evaluated the effects of acupressure on six meridian acupoints to reduce the stress, fatigue and anxiety of shift-work nurses, demonstrating that stress (p=0.043), fatigue (p<0.001), and anxiety (p=0.004) decreased significantly in comparison to the control group. 27 These results are comparable with another study that examined the effects of applying acupressure at the EX-HN3 point on pre-operative anxiety. 29 Similarly, a double-blind, randomised controlled trial examined acupressure therapy's effects on anxiety management in cancer patients.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…For example, one study evaluated the effects of acupressure on six meridian acupoints to reduce the stress, fatigue and anxiety of shift-work nurses, demonstrating that stress (p=0.043), fatigue (p<0.001), and anxiety (p=0.004) decreased significantly in comparison to the control group. 27 These results are comparable with another study that examined the effects of applying acupressure at the EX-HN3 point on pre-operative anxiety. 29 Similarly, a double-blind, randomised controlled trial examined acupressure therapy's effects on anxiety management in cancer patients.…”
supporting
confidence: 81%
“…24 Several earlier studies have revealed the efficacy of acupressure therapy for symptom relief in insomnia, premenstrual syndrome, dysmenorrhoea, during and after labour, reduction of nausea and vomiting, and reducing fatigue prior to and post-treatment. 20,[25][26][27][28] Findings from these studies also suggested that acupressure therapy can significantly reduce anxiety scores. For example, one study evaluated the effects of acupressure on six meridian acupoints to reduce the stress, fatigue and anxiety of shift-work nurses, demonstrating that stress (p=0.043), fatigue (p<0.001), and anxiety (p=0.004) decreased significantly in comparison to the control group.…”
mentioning
confidence: 89%
“…Four trials ( 6 , 15 , 17 , 40 ) used open randomization of random numbers table, resulting in a high risk of bias in concealment. Twelve trials ( 9 , 11 , 13 , 20 – 23 , 28 , 33 , 39 , 41 , 43 ) without sufficient detail were regarded as having an unclear risk of bias in allocation concealment. The remaining trials were evaluated as having a low risk of bias in allocation concealment.…”
Section: Resultsmentioning
confidence: 99%
“…Acupressure efektif dalam memberikan bantuan langsung dari kecemasan (Au et al, 2015). Acupressure secara signifikan dapat menurunkan stres, kelelahan, dan kecemasan (Cho et al, 2021).…”
Section: Kajian Pustakaunclassified